Computing Bodies : Gender Codes and Anthropomorphic Design at the Human-Computer Interface - Draude, Claude (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
Claude Draude analyzes embodied software agents - interface solutions that are designed to talk back and give emotional feedback - from a gender and media studies perspective. She addresses technological and sociocultural concepts in their interplay of shifting the boundary between what is considered as human and what as machine. The author discusses the technological realization of specific personality models that define the design of embodied software agents - emotion and gaze models, in particular. Finally, she explores these models in their broader cultural context by relating them to the prominent topic of the Turing test and the notion of the Uncanny Valley. Contents The Human-Computer Interface Semiotic Mirrors: The Interface as a Place of Sign/Signal Mediating Embodiment: The Role of the Body, Gaze Behavior and Emotions Counting as Machine, Counting as Human Target Groups Researchers and students in the fields of media studies, computer science, cultural studies, gender studies, sociology The Author Prof. Dr. Claude Draude is head of the department for Gender/Diversity in Informatics Systems (GeDIS) at the Faculty of Electrical Engineering/Computing at the University of Kassel, Germany.
Keywords: Social sciences.; Communication.; Sociology.; Mass media.; elektronické knihy; electronic books